2005
DOI: 10.1155/2005/312357
|View full text |Cite
|
Sign up to set email alerts
|

Safety Issues Concerning the Medical Use of Cannabis and Cannabinoids

Abstract: Safety issues are a major barrier to the use of cannabis and cannabinoid medications for clinical purposes. Information on the safety of herbal cannabis may be derived from studies of recreational cannabis use, but cannabis exposure and effects may differ widely between medical and recreational cannabis users. Standardized, quality-controlled cannabinoid products are available in Canada, and safety profiles of approved medications are available through the Canadian formulary. In the present article, the eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 108 publications
2
21
0
Order By: Relevance
“…Preparation protocol for APIs extraction sometimes included a preheating step, to enhance the yield of decarboxylation of acid‐APIs (THCA, CBDA): this optional step, and the lack of a standardized temperature and time, greatly contributes to a possibly clinically relevant interlot variability in APIs concentrations (Figure ), as well as to the variability in THCA/THC/CBN or CBDA/CBD ratios …”
Section: Discussionmentioning
confidence: 99%
“…Preparation protocol for APIs extraction sometimes included a preheating step, to enhance the yield of decarboxylation of acid‐APIs (THCA, CBDA): this optional step, and the lack of a standardized temperature and time, greatly contributes to a possibly clinically relevant interlot variability in APIs concentrations (Figure ), as well as to the variability in THCA/THC/CBN or CBDA/CBD ratios …”
Section: Discussionmentioning
confidence: 99%
“…31 One laboratory study showed that the euphoric effects of single doses of intravenously (0.25 mg) and orally (2 mg) administered nabilone were less pronounced than for $ 9 -THC (17.5 mg oral and 2.2 mg intravenous). 33 Similarly, another laboratory study showed that smoked cannabis (1.83% $ 9 -THC), but not 2 mg oral nabilone, increased elation factor scores on the Profile of Mood States.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids should generally be considered as a third line of treatment. A recent symposium of articles published in this Journal provide further information regarding the use of cannabinoids in pain (259,(270)(271)(272)(273)(274)(275)(276).…”
Section: Cannabinoids Cannabinoids Available By Prescriptionmentioning
confidence: 99%